Myocardial contrast echocardiography in the diagnosis of a left ventricular hemangioma - Kyriacos Papadopoulos; Constantinos Makrides (Italian Journal of Medicine, 2016)
Myocardial perfusion contrast echocardiography is an imaging tool for the assessment of myocardial microcirculation. It can also be used for the evaluation of the relative perfusion of a cardiac mass. Cardiac hemangiomas are rare tumors, accounting for only 2.8% of all benign primary cardiac tumors. We report a case of a 17-year-old man with a left ventricular hemangioma detected with transthoracic echocardiography. Myocardial perfusion contrast echocardiography was used to evaluate the vascularity of the cardiac mass. Using this technique malignant and hypervascular (e.g., hemangioma) tumors display persistence of contrast enhancement compared to the surrounding myocardium. The mass was successfully removed and the final report from pathology showed that the left ventricular mass was a hemangioma, a hypervascular tumor